2021
DOI: 10.4102/ajlm.v10i1.1057
|View full text |Cite
|
Sign up to set email alerts
|

From benchmarking to best practices: Lessons from the laboratory quality improvement programme at the military teaching hospital in Cotonou, Benin

Abstract: Background: In 2015, the Army Teaching Hospital–University Teaching Hospital (HIA-CHU [Hôpital D’instruction des Armées de Cotonou Centre Hospitalier et Universitaire]) laboratory in Benin launched a quality improvement programme in alignment with the World Health Organization Regional Office for Africa’s Stepwise Laboratory Improvement Process Towards Accreditation (SLIPTA). Among the sub-Saharan African laboratories that have used SLIPTA, few have been francophone countries, and fewer have belonged to a mili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 11 publications
(15 reference statements)
1
6
0
Order By: Relevance
“…Forty-one percent of the analysed studies revealed personnel motivation as key to successful QMS implementation. 26 , 28 , 30 , 31 , 37 , 41 , 42 , 44 , 45 , 47 , 48 , 49 , 53 Our results correspond to the findings of other studies that have recognised the psychological aspect of organisational changes and individual change acceptance as key components of success in healthcare innovation. 57 , 58 …”
Section: Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…Forty-one percent of the analysed studies revealed personnel motivation as key to successful QMS implementation. 26 , 28 , 30 , 31 , 37 , 41 , 42 , 44 , 45 , 47 , 48 , 49 , 53 Our results correspond to the findings of other studies that have recognised the psychological aspect of organisational changes and individual change acceptance as key components of success in healthcare innovation. 57 , 58 …”
Section: Resultssupporting
confidence: 89%
“…Most of the studies included in this review were conducted in Africa: Ethiopia ( n = 6), Kenya ( n = 4), Tanzania ( n = 3), Lesotho ( n = 3), Botswana ( n = 2), Nigeria ( n = 2), Cameroon ( n = 2), Mozambique ( n = 2), Rwanda ( n = 1), Zambia ( n = 1), Ghana ( n = 1), Zimbabwe ( n = 1), and Benin ( n = 1). 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 Studies reporting data from the Southeastern Asian countries (Cambodia [ n = 2], Vietnam [ n = 2]), 50 , 51 , 52 , 53 the Caribbean Region ( n = 1), 54 and Armenia ( n = 1) 55 were also included in the analysis (Supplementary Table 1). We found no relevant studies conducted in Eastern Europe (Ukraine, Belarus, Moldova, Romania, etc.)…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations